Localization of dimethylated histone three lysine four in the Rattus norvegicus sperm genome†. Issue 2 (28th February 2018) - Wilson, Shelby; Dere, Edward; Klein, David; Schorl, Christoph; Hall, Susan; Boekelheide, Kim
Abstract: We examined the precise localization of dimethylated histone three lysine four (H3K4me2) in mature rat sperm. Within nonintergenic-enriched regions, half of the DNA peaks associated with H3K4me2 retention fell in gene bodies and the other half in promoter regions. The most significant peaks near annotated DNA regions in the composite data included loci known to be associated with RNA metabolism, cell cycle regulation, and spermatogenesis. Regions associated with differential retention of H3K4me2 within gene bodies were significantly enriched for housekeeping gene and cell-cycle functionality. Proximal promoter-associated peaks were enriched for viral reproduction and cell cycle regulation genes, while Promoter1k and Promoter3k peaks were enriched for RNA metabolism functions. Further, homeobox- and kruppel-like factor motifs were among the most significantly enriched de novo and known motifs discovered within gene-associated H3K4me2 peaks. Motif analysis and native chromatin immunoprecipitation followed by sequencing (nChIP-seq) peak calling indicated an instructive role for retained paternal histones in the epigenetic regulation of early embryonic development in the rat.